Ionising radiation causes vision impairment in neonatal B6C3F1 mice. (March 2021) - Pawliczek, Daniel; Fuchs, Helmut; Gailus-Durner, Valerie; Hrabě de Angelis, Martin; Graw, Jochen; Dalke, Claudia
Abstract: Ionising radiation interacts with lenses and retinae differently. In human lenses, posterior subcapsular cataracts are the predominant observation, whereas retinae of adults are comparably resistant to even relatively high doses. In this study, we demonstrate the effects of 2 Gy of low linear energy transfer ionising radiation on eyes of B6C3F1 mice aged postnatal day 2. Optical coherence tomography and Scheimpflug imaging were utilised for the first time to monitor murine lenses and retinae in vivo . The visual acuity of the mice was determined and histological analysis was conducted. Our results demonstrated that visual acuity was reduced by as much as 50 % approximately 9 months after irradiation in irradiated mice. Vision impairment was caused by retinal atrophy and inner cortical cataracts. These results help to further our understanding of the risk of ionising radiation for human foeti ( ∼ 8 mo), which follow the same eye development stages as neonatal mice. Highlights: Ionising radiation causes cortical cataracts and retinal dysplasia in neonatal mice. Optical coherence tomography as monitoring tool for posterior cataracts. Imaging of cortical cataract revealed changing scattering properties. First revealed lens extrusions after exposure to a moderate dose of ionising radiation. Whole-body irradiation impairs visual acuity of neonatal mice.